Uji Sitotoksik Kuantitatif Ekstrak Biji Srikaya (Annona squamosa L.) pada Kultur Sel Limfosit T Pasien SLE In Vitro - Anindhito Kurnia Pratama; . Balgis; . Mujosemedi (Nexus Biomedika, 2013)
Background: Systemic Lupus Erythematosus is an autoimmune disease, mediated by lymphocytes. Methanol extract of Annona squamosa L. seed contains acetogenin, which can inhibit formation of ATP in the abnormal cell that acts as a source of energy that has selective properties of the abnormal cells only. The purpose of this study was to know the cytotoxic effects of Annona squamosa L. seed extract on T lymphocyte cell cultures of SLE patient in vitro. Methods: This study was an experimental laboratory research with post-test control group design. The sample was T lymphocyte cultures of SLE patients in the active phase. Cytotoxic effects of Annona squamosa L. seed extract on T lymphocyte cell culture of SLE patient in vitro were measured with the MTT assay then analyzed with regression analysis to determine the inhibitory concentration of fifty (IC50). Results: The IC50 of methanol extract of Annona squamosa L. seed on lymphocyte cell cultures of SLE patients was 0.17 g/mL, active criteria and normal sample was 0.06 g/mL., active criteria. While IC50 of cyclophosphamide for treatment of SLE samples was 16.80 g/mL and for normal sample was 39.24 g/mL. Conclusions: Based on this research, methanol extract of Annona squamosa L. seed had cytotoxic effects on lymphocyte cell cultures of SLE patient in vitro with active IC50 criteria Keywords: SLE, Annona squamosa L. seed, cytotoxic, T lymphocyte, IC50